Preparation and characterization of hydrogels from grafting of vinyl pyrrolidone onto carboxymethyl cellulose - Ahmad, Mansor; Hashim, Kamaruddin; Mohd Yazid, Norhanifah; Zainuddin, Norhazlin (Universiti Putra Malaysia Press, 2012)

(untitled)
In this work, hydrogels were prepared from carboxymethyl cellulose (CMC) and 1-vinyl-2-pyrrolidone (VP) by Electron Beam irradiation in the presence of N,N’-methylenebisacrylamide (BIS) as a crosslinking agent. The parameters studied include stirring time and percentage of crosslinking agent. Hydrogels were characterized using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM). VP and BIS were found be effective as reinforcement materials to improve the properties of CMC. Meanwhile, the optimum conditions were 5% BIS and 3 hours of stirring time. The gel fraction increased when irradiation dose was increased. FTIR confirmed the crosslinking reaction between CMC and VP after the irradiation process by using BIS as the crosslinking agent. TGA thermograms showed changes in the thermal properties of CMC-VP hydrogels in the presence of different amounts of BIS.